Attention To Entrepreneurial Women in The Republic of Uzbekistan - Boltayeva Mohichexra Jamshid qizi; Murotjonova Mubina Dilshod qizi (Global Scientific Publishing, 2022)
This article discusses the role of women and girls in society in the Republic of Uzbekistan, social, economic and spiritual freedom, the attention and conditions shown to women and girls.
Keywords: New Uzbekistan; active women; women's interests; gender equality